2020
DOI: 10.1038/s41467-020-16022-0
|View full text |Cite
|
Sign up to set email alerts
|

A phenome-wide association and Mendelian Randomisation study of polygenic risk for depression in UK Biobank

Abstract: Depression is a leading cause of worldwide disability but there remains considerable uncertainty regarding its neural and behavioural associations. Here, using non-overlapping Psychiatric Genomics Consortium (PGC) datasets as a reference, we estimate polygenic risk scores for depression (depression-PRS) in a discovery (N = 10,674) and replication (N = 11,214) imaging sample from UK Biobank. We report 77 traits that are significantly associated with depression-PRS, in both discovery and replication analyses. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 71 publications
6
48
0
Order By: Relevance
“…In over 9,000 participants from UK Biobank, Shen et al . (51) recently found PRS for MDD was associated with white matter integrity of several tracts, such as the SLF, the cingulate gyrus part of cingulum, the inferior fronto-occipital fasciculus and superior thalamic radiation, which were associated with PRS-anhedonia in our study. Previous studies on PRS for MDD have also reported associations with decreased white matter integrity, most notably in the SLF, cingulum and thalamic radiations (52-54), although null findings have also been reported with respect to polygenic risk for MDD or schizophrenia (39, 55).…”
Section: Discussionsupporting
confidence: 72%
“…In over 9,000 participants from UK Biobank, Shen et al . (51) recently found PRS for MDD was associated with white matter integrity of several tracts, such as the SLF, the cingulate gyrus part of cingulum, the inferior fronto-occipital fasciculus and superior thalamic radiation, which were associated with PRS-anhedonia in our study. Previous studies on PRS for MDD have also reported associations with decreased white matter integrity, most notably in the SLF, cingulum and thalamic radiations (52-54), although null findings have also been reported with respect to polygenic risk for MDD or schizophrenia (39, 55).…”
Section: Discussionsupporting
confidence: 72%
“…We estimated PRS for N = 29,879 participants with quality controlled genetic and imaging data, using effect sizes for each allele from a large prior GWAS of 7,585,078 SNPs in N = 69,369 schizophrenia cases and N = 236,642 healthy controls [5]. We constructed eight polygenic scores with varying P SNP -value thresholds ( P SNP ≤ 0.0001, ≤ 0.001, ≤ 0.01, ≤ 0.1, ≤ 0.25, ≤0.5, ≤ 0.75, ≤ 1) for each individual [20, 41]. PRS’s were normally distributed at all P SNP -value thresholds ( SI Methods ) and the number of SNPs included in the calculation at each probability threshold is reported in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…We constructed eight polygenic scores with varying P SNP -value thresholds (P SNP ≤ 0.0001, ≤ 0.001, ≤ 0.01, ≤ 0.1, ≤ 0.25, ≤ 0.5, ≤ 0.75, ≤ 1) for each individual [20,41]. PRS's were normally distributed at all P SNP -value thresholds (SI Methods) and the number of SNPs included in the calculation at each probability threshold is reported in Table S1.…”
Section: Polygenic Risk Scoresmentioning
confidence: 99%
“…All analyses were conducted using R (version 3.2.3) in a Linux environment. Linear mixed-effects models (function ‘lme’ in R package ‘nlme’) and general linear models (function ‘glm’ in R package ‘stats’) were used to investigate structural brain metrics 46,47 False Discovery Rate (FDR) multiple comparison correction was applied to all bilateral/unilateral structures, lobes and white matter tracts, referred to as P FDR in this report, using the ‘p.adjust’ function in R and all betas were standardised. FDR correction was also applied over each sub-analysis.…”
Section: Methodsmentioning
confidence: 99%